1992
DOI: 10.1111/j.1365-2141.1992.tb06947.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of the hybrid Bcr‐Abl RNA in patients with chronic myelogenous leukaemia under interferon therapy

Abstract: In vitro amplification of the Bcr-Abl cDNA has been widely used to assess for the presence of minimal residual disease in patients with chronic myelogenous leukaemia (CML) presenting with complete clinical and cytogenetic remission. However, the level of sensitivity achieved in different laboratories remains largely unknown. Moreover, the results are usually expressed as positive or negative, making a precise follow-up of the patients difficult. In an attempt to overcome these limitations, we devised a quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…In fact, our results confirm those of Lee et al 7 and Hochhaus et al 12 who reported that all complete cytogenetic responders on IFN-␣ have detectable residual disease by two-step RT-PCR independent of the duration of CCR. Although at least 23 cases have been reported 12,13,[16][17][18][19][20][21][22][23] with intermittent or persistent PCR negativity on IFN-␣ using different PCR techniques, these observations may be due to the considerable variability in the sensitivity of PCR techniques performed in different laboratories. Consequently, the PCR negativity reported in CCR patients could be due more to technical discrepancies among different laboratories than to a real cure of the patients.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In fact, our results confirm those of Lee et al 7 and Hochhaus et al 12 who reported that all complete cytogenetic responders on IFN-␣ have detectable residual disease by two-step RT-PCR independent of the duration of CCR. Although at least 23 cases have been reported 12,13,[16][17][18][19][20][21][22][23] with intermittent or persistent PCR negativity on IFN-␣ using different PCR techniques, these observations may be due to the considerable variability in the sensitivity of PCR techniques performed in different laboratories. Consequently, the PCR negativity reported in CCR patients could be due more to technical discrepancies among different laboratories than to a real cure of the patients.…”
Section: Discussionmentioning
confidence: 77%
“…Taking advantage of a linear relationship between the input template (usually cDNA obtained after RT from extracted total RNA) and amplification product within the exponential range of PCR, several authors have also reported a competitive PCR assay for quantification of bcrabl amplified transcript. [10][11][12][13] We have developed a similar competitive quantitative RT-PCR assay associated with amplified bcr-abl transcript quantification based on a capillary electrophoresis spectrophotometric analysis (CE). 8 We applied this method to evaluate the level of bcr-abl transcript at diagnosis and at the time of major (Ͼ66% Ph negativity) or complete cytogenetic remission (100% Ph negativity) in a restricted group of CML patients after receiving IFN-␣-based therapy, sometimes followed by autologous bone marrow transplantation.…”
mentioning
confidence: 99%
“…In CML the fusion BCR/ABL gene is tested in parallel with a control ABL gene and the amount of BCR/ABL transcript is related to the total mount of ABL transcript. 19,33,34 However, as the tested ABL fragment is present not only in the normal ABL gene but also in the BCR/ABL fusion gene, some objection can be raised.…”
Section: Discussionmentioning
confidence: 99%
“…In a typical noncommercial Q-RT-PCR assay, for which many variations exist (Lion et al, 1992;Malinge et al, 1992;Thompson et al, 1992;Cross et al, 1993), cDNA of an internal reference, such as ␤2 microglobulin or ABL, is co-amplified in the same tube as cDNA of BCR-ABL to control for variations in the procedures such as sample preparation and loading. PCR products are then analyzed by gel electrophoresis and densitometry.…”
Section: Quantitative Rt-pcrmentioning
confidence: 99%